Effect of tobacco smoking on the skin - Sałata-Nowak, Justyna; Flisiak, Iwona; Chodynicka, Bożena (Dermatology Review/Przegląd Dermatologiczny, 2010)
Tobacco smoking is considered to be one of the main factors which negatively affect the skin, mucous membranes and teeth. Apart from nicotine, smoke contains many toxic substances, with several carcinogens among them. The relationship between smoking and wound healing, skin ageing, skin cancers, neoplasms of mucous membranes, psoriasis, palmoplantar pustulosis, hidradenitis suppurativa, genital warts and Buerger’s disease is well documented. The influence of smoking on the course of diseases such as acne, hand eczema or malignant melanoma is still a theme of discussion. However, smoking also has a beneficial effect on some diseases, such as pyoderma gangrenosum, pemphigus vulgaris, aphthous and genital ulcers in Behçet's disease, acral melanoma or labial herpes and Kaposi’s sarcoma in AIDS patients.